Disfungsi Media Sosial dalam Seruan Pemerintah: Lemahnya Pengaruh Konten Instagram terhadap Pelaksanaan Protokol Kesehatan Covid-19 - Rian Ervina Nugraha; Lukman Nusa (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2022)
In early 2020, the coronavirus disease (covid-19) has reached Indonesia and is rapidly spreading. The Province of the Special Region of Yogyakarta is the area with the lowest positive number of covid-19 compared to other provinces on the island of Java. This is certainly inseparable from the decision of the Yogyakarta’s Government, one of which is communication on the @humasjogja Instagram account. Through the content produced, the Instagram account @humasjogja actively urges its followers to be vigilant and comply with the health protocol of covid-19. For this reason, it would be interesting if there was research to determine the magnitude of the influence of Instagram content on the implementation of the COVID-19 health protocol. To answer this problem, Media Dependency Theory is suitable to be used as a research basis because this theory explains that media that can provide individual desires will be considered important and can affect individual behavior changes. This study uses a survey research method to 100 respondents who are followers of the Instagram account @humasjogja and uses a simple linear regression analysis method. The results of the study found that there was an effect of 35.9% of Instagram content on the implementation of the covid-19 health protocol on followers of the Instagram account @humasjogja, and showed a scale of influence that was at a weak level.Keywords: Social Media, Instagram Content, Covid-19, Health Protocol of Covid-19.